Neuroimaging and neurocognitive assessment of PTSD and MDD in a South African community setting - Koopowitz, Sheri (Department of Psychiatry and Mental Health, 2019)
Background: There is growing evidence of abnormalities in neurocognition, neuroanatomy, and functional connectivity in posttraumatic stress disorder (PTSD) and major depressive disorder (MDD). However, there has been less work on individuals who suffer with comorbid PTSD and MDD. It is important to investigate the neurobiology of this overlap because of its prevalence, its associated morbidity, and the hope that it may shed more light on the mechanisms involved in each disorder, including the role of the prefrontal regions. This dissertation tests the hypothesis that women with PTSD and MDD display distinct patterns of neurocognitive impairment and associated brain dysfunction, relative to healthy controls, and these effects will be amplified in patients with both disorders. Methods: This dissertation was undertaken within the Drakenstein Child Health Study, a study exploring child health determinants in mother-infant dyads from the Drakenstein district, Western Cape. Mothers (between 18 and 50 years) were recruited and divided into 4 groups: PTSD, MDD, PTSD with MDD, and healthy controls. Participants were assessed using the computerised NIH Toolbox, and paper and pencil neurocognitive tests. Domains assessed included memory, learning, and processing speed, and with particular focus on executive function and attention domains. Participants underwent resting-state functional imaging as well as structural brain imaging. Functional connectivity within and between cognitive control networks (salience network, dorsal attention network, and frontoparietal networks) and a default mode network were compared across the 4 groups. Neuroanatomical indices (cortical thickness, volume, and surface area) of 10 frontal cortical regions from the Desikan-Killiany atlas in Freesurfer 6 were analysed across the 4 groups. Results: All three clinical groups demonstrated no group differences on measures of attention and executive function, diagnoses of PTSD and MDD were associated with more intrusive thoughts and delayed recall impairment, respectively. However, neurocognitive findings indicate that PTSD with comorbid MDD is not associated with greater neurocognitive dysfunction relative to mono-diagnostic groups. Abnormal resting-state connectivity was observed for the MDD group in the default mode network, and for both comorbid and MDD patient groups within frontoparietal networks. Abnormal salience network connectivity for the comorbid group was observed when examining performance on the Pattern Comparison Processing Speed test. No between-network connectivity group differences were observed. Surface area and volume reductions of prefrontal regions were evident for PTSD and MDD, however, no volumetric and surface area differences were observed for the comorbid group. Conclusion: In this sample of mothers from a low-middle income region, distinct patterns of neurocognitive dysfunction and impairment in PTSD, MDD, and PTSD with MDD were observed. However, contrary to hypotheses, comorbidity is not associated with greater dysfunction and impairment and the associations of PTSD and comorbid MDD are not amplified in this sample. These findings have implications for the development of treatment plans for patients diagnosed with PTSD, MDD, and PTSD with comorbid MDD, so that interventions are tailored in a way that is responsive to differences between these groups in the presentation of neurocognitive profile, brain function, and structure.